2019
DOI: 10.1016/j.ebcr.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Ability to knit may be impaired following right temporal lobe resection for drug-resistant epilepsy

Abstract: HighlightsThe ability to knit may be compromised following a right or non-dominant temporal lobe resection.Non-lesional patients may be at particular risk.It is important to disseminate knowledge of impact of epilepsy surgery on specialist skills, via case studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The fronto-central theta rhythm generators involved with knitting may overlap with the TR, given their similar electrographic appearance while performing tasks of interest involving motor movements of the bilateral fingers and hands [4]. However, knitting involves complex pattern recognition and visuospatial processing that is unique from TR [7]. Yoon and colleagues recently reported that increased occipital–cerebellar gray matter identified with source-based morphometry was significantly correlated with improved speed on the trailmaking test-A, which requires visuospatial search and processing speed similar to knitting [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fronto-central theta rhythm generators involved with knitting may overlap with the TR, given their similar electrographic appearance while performing tasks of interest involving motor movements of the bilateral fingers and hands [4]. However, knitting involves complex pattern recognition and visuospatial processing that is unique from TR [7]. Yoon and colleagues recently reported that increased occipital–cerebellar gray matter identified with source-based morphometry was significantly correlated with improved speed on the trailmaking test-A, which requires visuospatial search and processing speed similar to knitting [8].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the fronto-central theta rhythm involved with knitting has a primary generator involving prefrontal cortex concentration processing and motor planning in the supplementary motor area (part of the medial prefrontal cortex), with network connectivity to the primary motor cortex. Furthermore, there is likely variable input from parieto-occipital–cerebellar cortex directed visuospatial processing and the parietal somatosensory cortex [7]. Prior scalp EEG source localization of 4 patients with TR was also notable for mesial frontal lobe predominance [9].…”
Section: Discussionmentioning
confidence: 99%